MEMS optical switches. - Yeow, Tze-Wei
Leveraging MEMS's inherent advantages such as the batch fabrication technique, small size, integrability, and scalability, MEMS is positioned to become the dominant technology in optical crossconnect switches. MEMS optical switches with complex movable 3D mechanical structures, micro-actuators, and micro-optics can be monolithically integrated on the same substrate by using the matured fabrication process of the integrated circuit industry. In this article we report various popular actuating mechanisms and switch architectures of MEMS optical switches. The basics of surface and bulk micromachining techniques used to fabricate MEMS devices are reviewed. Examples of 2D and 3D approaches to MEMS optical switches are described. The pros and cons of the two approaches are analyzed. In the short term, MEMS-based optical switches seem to have captivated the attention of both the industry and academia. However, there are challenges that threaten the long-term survival of this technology. The problems that remain to be fully addressed are discussed
Keywords: 2D approaches; 3D approaches; MEMS optical switches; Actuating mechanisms; Batch fabrication technique; Bulk micromachining; Complex movable 3D mechanical structures; Integrability; Micro-actuator.; Optical crossconnect switches; Scalability; Size; Surface micromachining; Switch architectures